Forms of Difference in Sorcières. Issue 3 (3rd July 2019) - Spencer, Catherine
Abstract: Art practice and organizing occupied a significant but precarious place in the groups and networks that made up the Mouvement de libération des femmes (MLF) in France during the 1970s. This was reflected in the relatively small amount of space allocated to analyzing the relationships between visual production and feminist politics in the art press and activist publications alike. There was, however, one significant exception to this general rule: the journal Sorcières (1975–1982) which, although a predominantly literary initiative, regularly featured original contributions by contemporary women artists working in the context of the MLF, as well as reviews of exhibitions and statements by practitioners. Sorcières was particularly invested in exploring notions of women's difference and alternative expression, notably through écriture féminine. Yet the publication did not adopt an exclusively essentialist position, or focus on embodiment to the outright dismissal of materialist concerns. This openness is especially apparent in the journal's engagement with visual art, resulting partly from the key contribution made by members of the Collectif Femmes/Art. Visual production, this article contends, thus played a key role in the exploration of various forms of difference across the pages of Sorcières .